Determination and classification of the technical means of copyright protection - Пономаренко, Олександр Васильович; Молодід, Владислав Юрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article is devoted to the the technical means of copyright protection. It defines the determination of the technical means of copyright protection, it's place among other civil means of protection, grounds of classification and reasons for it.